Print to Braille: Preparation and Accuracy of Mathematics Materials in K-12 Education. (September 2014) - Herzberg, Tina S.; Rosenblum, L. Penny
Introduction: This study analyzed the accuracy of 107 mathematics worksheets prepared for tactile learners. The mean number of errors was calculated, and we examined whether there was a significant difference in the level of accuracy based on National Library Service for the Blind and Physically Handicapped (NLS) certification or job role of participants. Methods: The authors selected five work sheets representative of mathematics materials transcribed for K-12 students. After completing an online demographic survey, participants prepared at least one of the worksheets and completed an online transcription survey about how they prepared each worksheet. Results: The majority of the 59 participants spent less than 30 minutes transcribing each worksheet, and the predominant method for production was the use of braille translation software. Overall, participants had a high level of accuracy on the literary braille portions of the worksheets. There was variability in the accuracy of the Nemeth elements, formatting, and tactile graphic labels across the transcriptions. Significant differences existed between the means of errors in formatting and literary braille according to NLS certification status and, to a lesser extent, job role. There was not a significant difference in the accuracy of Nemeth elements in the majority of the worksheets according to certification status or job role. There were no significant differences in the preparation of the worksheets based on primary production method. Discussion: There was variability in how materials were prepared for tactile readers and in the quality of the transcriptions. Implications for practitioners: Variation in how materials are presented to tactile readers, including the formatting of headings and directions, can affect the ease of scanning and reading of materials. Inconsistencies, omissions, and errors have the potential to impact the ability of readers to understand and access information.